Public perception about the Zika virus in working professionals: a qualitative inquiry - Choudhry, Riaz Fahad; Munawar, Khadeeja; Kassab, Yaman Walib; Bakrin, Faizah Safina; Al-Worafi, Yaser Mohammed; Khan, Tahir Mehmood (SAGE Publications Inc., 2020)
Aims: The Global Outbreak Alert and Response Network recently warned that the Zika virus-containing mosquitoes are being found in Pakistan and the health sector is on high alert. It is thus significant to understand public beliefs and perceptions of the Zika virus and vaccination in the current scenario of Pakistan. Methods: Twenty semistructured qualitative interviews were conducted and analyzed through an inductive approach to analysis. Results: The findings were presented in three main categories which were coded: Reality vs. Conspiracy, Vaccination Concerns, and Public Worries. The majority believed that the Zika virus is a real problem and that authorities might be trying to hide the Zika cases in Pakistan. Moreover, they believed that health organizations are being incompetent by failing to take timely remedial measures to manage the Zika. However, 20% have an opposing view and believed that the Zika virus is a conspiracy against Pakistan from the West. Conclusion: Overall, most participants were concerned about the lack of treatment and preventive methods and emphasized the need to create awareness among the public. It is observed that the participants’ perceptions ranged from perceiving the Zika virus as real to as a conspiracy. © The Author(s) 2020.